Money, credit and inflation : an historical indictment of UK monetary policy and a proposal for change - Pepper, Gordon (London: Institute of Economic Affairs, 1990)
This publication examines the British economy with specifica reference to money supply, inflation, monetary policy and exchange rates.
Includes bibliographical references.
lje 13/9/13
Loans
Keywords: Inflation -- Finance -- Great Britain; Monetary policy -- Great Britain